In defense of globalization - Bhagwati, Jagdish N., 1934 (Oxford University Press, 2007)
In the passionate debate over globalization, critics have blamed it for a host of ills afflicting poorer nations, everything from child labor to environmental degradation and cultural homogenization. Now the economist, Bhagwati, reveals that globalization, when properly governed, is in fact the most powerful force for social good in the world today.